El duelo y el tiempo mítico en Rosa Cuchillo y La hora azul - Torres Oyarce, Tania (2017)
In this paper, I propose that the novels Rosa Cuchillo and La hora azulproject individual processes of mourning in a mythical social order thatlimits itself to reproduce the phantom of the enclosed nation (Ubilluz) asa (seudo) proposal to solve the internal conflict that took place in Perubetween 1980-2000. In Rosa Cuchillo the main character, Rosa Cuchillo,goes through a process of mourning due to the loss of his terrorist son,Liborio, whereas in La hora azul the main character, Adrián Ormache,undergoes a process of mourning due to the crisis of the idealized paternalfigure he had of his dead military father. These individual experiences ofmourning result in an opening to the social order by means of the mythof the eternal return (Debord) in Rosa Cuchillo and the myth of progress(Benjamin) in La hora azul. Located in a mythical time, the social consequencesof the novels become apparent: they reproduce proposals thatdo not question the phantom of the enclosed nation, since Rosa Cuchilloproposes a pachacuti of runas, whereas La hora azul suggests a form oftutelary ethics that maintains the status quo.